2019
DOI: 10.1186/s13071-019-3446-3
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric dengue infection in Cirebon, Indonesia: a temporal and spatial analysis of notified dengue incidence to inform surveillance

Abstract: Background The recent situation of dengue infection in Cirebon district is concerning due to an upsurge trend since the year 2010. The largest dengue outbreak was reported in 2016 which has affected more than 1600 children. A study was conducted to explore the temporal variability of dengue outbreak in Cirebon’s child population in during 2011–2017, and to assess the short-term effects of climatic and environmental factor on dengue incidence. In addition, the spatial pattern of dengue incidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 54 publications
(67 reference statements)
4
28
0
1
Order By: Relevance
“…The monsoon is correlated with an extended period of rainy and wet days, and higher temperatures, which are favourable for mosquito breeding and population expansion [ 15 , 16 ]. The finding is consistent with studies conducted in Indonesia [ 22 ], Timor-Leste [ 47 ] and Sri Lanka [ 48 ], which demonstrated an increasing number of cases during the monsoon and hottest season.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The monsoon is correlated with an extended period of rainy and wet days, and higher temperatures, which are favourable for mosquito breeding and population expansion [ 15 , 16 ]. The finding is consistent with studies conducted in Indonesia [ 22 ], Timor-Leste [ 47 ] and Sri Lanka [ 48 ], which demonstrated an increasing number of cases during the monsoon and hottest season.…”
Section: Discussionsupporting
confidence: 92%
“…Ten-day composites of 250-m spatial resolution normalized difference vegetation index (NDVI) data for the study period were obtained from the U.S. Geological Survey's (USGS) Earth Resources Observation and Science (EROS) Moderate Resolution Imaging Spectroradiometer (eMODIS) ( https://earthexplorer.usgs.gov/ ) [ 31 ]. NDVI indicates vegetation greenness and is often used as a proxy for mosquito-favoured habitats [ 22 ]. Prior to analysis, three 10-day composited raster images were used to obtain mean NDVI values by monthly windows for the study area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using local indicators of spatial association (LISA) map, we clustered in the significant spatial autocorrelation regions and displayed them in the form of significant and clustering graphs 38,39 . Four spatial patterns could be seen intuitively in LISA maps 40 , high-high (high-incidence regions surrounded by high-incidence regions, which are highly epidemical regions), low-low (low-incidence regions surrounded by low-incidence regions, which are lowly epidemical regions), high-low (high-incidence regions surrounded by low-incidence regions) and low-high (low-incidence regions surrounded by high-incidence regions) 41,42 .…”
Section: Global Indicators Of Spatial Association (Gisa)mentioning
confidence: 99%
“…In Taiwan, temperature and precipitation influenced dengue incidence rates with a lag of 10–20 weeks [ 26 ]. In the context of dengue infection in Indonesia, studies have shown that dengue incidence is associated with temperature, rainfall, and humidity [ 45 , 46 , 47 ]. In this present study, those local climate variables (temperature, rainfall, and humidity), which might have had a stronger impact on chikungunya incidence, were not included.…”
Section: Discussionmentioning
confidence: 99%